Pengaruh Frekuensi Pelatihan Salesman Terhadap Volume Penjualan Studi Kasus pada PT. Dwiperkasa Mobiltama Bogor - Zuhdi, Saefudin; Natan, Christian Stefanus (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2007)
The purpose of this research is to find out training frequency done by a firm to increase selling volume and how far the influence of training to selling volume, and what obstacles the firm faces in increasing salesmans quality. The result of this research shows that training frequency done by the firm has low influence to selling volume. It can be proven by low correlation score, that is 0,426. From regression counting result, it can be found out Y = 231,87 + 49,47 X. It means, if training influence (X) moves up to 1 unit, selling volume will move up to 49,47 units. If there is no training, selling volume is 231, 87. Statistical test works in t-test. T-count score = 1,333 and t-table score = 1,860. Because of t-count score is lower than t-table score (1,333 < 1,860), the influence of training frequency to selling volume is not significant. Keywords: Training; Selling volume.